PERKEMBANGAN Spodoptera frugiperda J.E Smith PADA TANAMAN JAGUNG MANIS (Zea mays L. Saccharata) - Wilyus Wilyus; Hamdan Maruli Siregar; Rizki Aulia (Universitas Batanghari, 2021)
This study was conducted to determine the relationship between sweet corn plant phenology and population development and the attack of Spodoptera frugiperda. The research was carried out at the Research Farm and at the Laboratory of Plant Pests, Faculty of Agriculture, Jambi University. The study was conducted on an area of 500 m2 containing 28 plant plots. The sample plants consisted of 4 plots determined systematically. In each sample plot, all plants were used as sample. plants to calculate the percentage of attacked plants, and the percentage of attacked cobs. S. frugiperda population observations were carried out directly on leaves, stems, flowers and cobs. If there were S. frugiperda faeces on the shoots, stems, and cobs, destructive observations were made where the plant parts were opened, to determine the presence of S. frugiperda in them. The data obtained were tabulated and arranged in the form of tables and figures, then explained descriptively. The results showed that: the population of S. frugiperda in each growth phase continued to increase, the highest population of S. frugiperda was found in the R6 phase or in the physiological ripening phase, which was as many as 21 heads per 12 corn plants; the percentage of attacks of S. frugiperda in each phase continues to increase, the highest percentage of attacks is in phase R6, which is 78.72%; the attack of S. frugiperda on cobs began to be seen in the R2-R5 phase and was highest in the R6 phase, which was 68.57%. It is necessary to find the right way to control S. frugiferda.